El eco de las batallas: música y guerra en el bando nacional durante la contienda civil española (1936-1939) - Igor Contreras Zubillaga (Amnis)
This article, based on several unpublished archive sources, analyzes three works composed during the Spanish Civil War, closely related to the nationalist faction, whose theme revolves precisely around the war: Nemesio Otaño’s anthem ¡Franco!, ¡Franco!, Ernesto Halffter’s Amanecer en los jardines de España and Conrado del Campo’s Ofrenda a los Caídos. Through these three examples, we will try to outline a typology of patriotic music with an undeniable pro-Franco stamp. This perspective fits into a broader discussion on the artistic production under contexts of war, traditionally considered, until quite recently, as a parenthesis, specially regarding the field of music.